Motivation of Gender-Based Volleyball Athletes During Competitions : A Coach Athlete Relationship Perspective - Yonda Maisy Lalita; Mohammad Zaky; Unun umaran (Journal of Physical Education Health and Sport, 2025)
Motivation during competition is one of the important psychological factors that influence an athlete's performance in volleyball. This study aims to determine the relationship between motivation during competition and the coach-athlete relationship, as well as to analyze differences in motivation and the coach-athlete relationship based on gender among volleyball athletes. This study used a quantitative method with a correlational design and involved a sample of 40 volleyball athletes from the JVC Raya Club, consisting of 20 male athletes and 20 female athletes. The instruments used were the Sport Motivation Scale II (SMS-II) to measure motivation during competition and the Coach-Athlete Relationship Questionnaire (CART-Q) to measure the coach-athlete relationship. Data analysis was performed using Spearman's correlation test and the independent sample t-test. The results showed a significant and positive relationship between coach-athlete relationships and competition motivation (r = 0.863; p < 0.05). Meanwhile, the results of the difference test showed that there was no significant difference between male and female athletes on both variables, although descriptively female athletes had slightly higher average scores. This study shows that there is a significant and positive relationship between coach-athlete relationships and motivation during competition in volleyball athletes.